The Effect of Cash Conversion Cycle and Debt Ratio to Profitability (Listed Pharmaceutical Companies in Indonesia Stock Exchange) - admin, Devya Widhiyanti B42112001 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
This research aims at analyzing the effect of payable deferral period, cash conversion cycle and debt ratio in pharmaceutical sector companies listed on the Indonesia Stock Exchange from 2010 to 2014. The sample is selected by using purposive sampling method. The result shows that payable deferral period, cash conversion cycle and debt ratio simultaneously have a significant effect to profitability, because F-test value is 0.000 which is less than significant value 0,05. According to multiple regression analysis, payable deferral period has a negative insignificant influence to profitability. Whereas, cash conversion cycle has a positive significant influence to profitability, but the debt ratio has a negative significant influence to profitability. Â  Keywords: Payable Deferral Period, Cash Conversion Cycle, Debt Ratio and Profitability.